2017
DOI: 10.1016/j.chiabu.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Mental health indicators fifty years later: A population-based study of men with histories of child sexual abuse

Abstract: Childhood sexual abuse (CSA) is a widely acknowledged trauma that affects a substantial number of boys/men and has the potential to undermine mental health across the lifespan. Despite the topic's importance, few studies have examined the long-term effects of CSA on mental health in middle and late life for men. Most empirical studies on the effects of CSA have been conducted with women, non-probability samples, and samples of young or emerging adults with inadequate control variables. Based on complex trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 48 publications
2
62
1
2
Order By: Relevance
“…For example, although studies have found the link between childhood sexual abuse experiences and subsequent mental health, several such studies do not have information on additional adverse experiences from which to fully examine the relative contributions (e.g., Easton & Kong, 2016; Spataro, Mullen, Burgess, Wells, & Moss, 2004). The current study seeks to deconstruct the relationship between ACE score and mental health outcomes in adulthood by examining each ACE separately.…”
mentioning
confidence: 99%
“…For example, although studies have found the link between childhood sexual abuse experiences and subsequent mental health, several such studies do not have information on additional adverse experiences from which to fully examine the relative contributions (e.g., Easton & Kong, 2016; Spataro, Mullen, Burgess, Wells, & Moss, 2004). The current study seeks to deconstruct the relationship between ACE score and mental health outcomes in adulthood by examining each ACE separately.…”
mentioning
confidence: 99%
“…Most extant research is based on predominantly or exclusively female samples (Easton, 2014;Ullman & Filipas, 2005); this study expanded our understanding of sexually abused boys. Recent research has established that CSA can impact mental health across the life course and into late life (Easton & Kong, 2017). This study was one of the first to examine associations between childhood disclosure and long-term mental health for male survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Although family therapists have long included family of origin experiences as an essential component in psychological distress (e.g., Boszormenyi-Nagy & Krasner, 1986;Bowen, 1976;Diamond et al, 2016), systematic research on childhood adversity is individually focused, linking major emotional trauma in childhood to several severe health outcomes (Felitti et al, 1998). A robust connection among childhood abuse, neglect, and depressive and somatic symptoms has been established in multiple populations (Dube, 2018;Easton & Kong, 2017;McCall-Hosenfeld et al, 2014) along with increased rates of comorbidity (Tietjen et al, 2007). Recent research on psychobiological responses suggest patterns of cortisol dysregulation in adults with combined experiences of childhood adversity and current stressors, likely leading to an impaired capacity to cope (Young et al, 2020).…”
Section: Aces and Psychological Distressmentioning
confidence: 99%